Sistem Analisis Rekomendasi Saham Pada Indeks LQ45 Menggunakan Indikator Moving Average Convergence Divergence (MACD) dan Relative Strength Index (RSI) - Kalista Setiawan; Tristiyanto Tristiyanto; Anie Rose Irawati (Jurnal Komputasi, 2021)
The LQ45 stock index is a stock exchange that is in great demand by investors in Indonesia. Therefore, the movement of the stock price is needed by investors to see the investment business prospects. However, stock price movements in a certain period are very volatile. In this case, investors need a monitoring system to assist their investment decisions. One of the most popular analyzes of stock price movements is technical analysis. In this study, the system is a website that can be accessed by the public. It provides technical analysis indicators of Moving Average Convergence Divergence (MACD), Relative Strength Index (RSI), and Candlestick charts. The system uses the AnyChart JS component as a modern JavaScript library chart. The waterfall method is used to assist develop this system. The system consists of two sources API, namely Rakuten Rapid (APIdojo.net) and finnhub.io with a query provider that can connect the Yahoo Finance API. The results of stock recommendations in this system come from determining the largest value for several recommendations generated by the finnhub.io based on basic technical and aggregate analysis (MACD, RSI, and Moving Average). Thus, this recommendation is only a suggestion and cannot be used as an absolute reference.